2022
DOI: 10.1097/ncc.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Physical and Cognitive Function in Individuals With Head and Neck Cancer

Abstract: BackgroundHead and neck cancer (HNC) and associated treatments have significant long-term and late adverse effects that can impair function. Therefore, there is a need for reliable common metrics to assess function in HNC that limit participant burden and are cost-effective and easy to use in clinical settings.ObjectiveThe aim of this study was to assess the feasibility of using the Fitbit Zip, NIH Toolbox, and REDCap electronic data collection tool to measure function and symptoms in individuals with HNC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Decline in PA levels in the participants may be a treatment-related symptom or a part of a cluster of inflammation-associated conditions. In a previous prospective descriptive study, 41 daily step count was used as a measure for evaluating PA levels in newly diagnosed HNC patients undergoing curative (chemo)radiotherapy. The study found that in most participants, the nadir in step count was observed during or shortly after treatment, suggesting that changes in PA levels were likely related to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Decline in PA levels in the participants may be a treatment-related symptom or a part of a cluster of inflammation-associated conditions. In a previous prospective descriptive study, 41 daily step count was used as a measure for evaluating PA levels in newly diagnosed HNC patients undergoing curative (chemo)radiotherapy. The study found that in most participants, the nadir in step count was observed during or shortly after treatment, suggesting that changes in PA levels were likely related to treatment.…”
Section: Discussionmentioning
confidence: 99%